Implementation of Technologies in the Commercialization of Agricultural Products in Small and Medium Producers - Murillo-Salamanca, Víctor-Manuel; Chaparro-Barrera, Carlos-Fabián (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The agricultural production systems of Colombia have been established as an important productive sector of the country. A large percentage of the products that are generated come from small and medium-scale farms, which face great challenges that can affect their efficiency and productivity. One of the main drawbacks are the marketing strategies of the products, where there are actors who interact within the process such as intermediaries, who send the product to the final consumer, taking all the monetary gains. With the growing implementation of information technologies, strategies have been designed to offer the farmer an alternative marketing mechanism where he meets the final consumer; Within these are mobile applications, a tool that has allowed the sale of goods and services from different productive sectors. The objective of this literature review is to identify the usefulness of technologies in the commercialization of agricultural products in small and medium producers. An information search was carried out in the Google academic search engine, and in the Scielo, Redalyc, Science Direct, Scopus and Web of Science databases, implementing descriptors production, commercialization, production systems and technology. It was possible to establish that the applications allow to improve the producer-consumer relationship, in addition to reducing the number of intermediaries, improving the commercialization and the payment that the producer receives.